Efficacy of the Use of Audio-Visual Facilities in the Teaching and Learning of English Phonology - Benjamin F.C. Nwokedi (MultiTech Publisher, 2023)
This paper discussed the efficacy of the use of audiovisual facilities in the teaching and learning of English Phonology. In recent years, the integration of audiovisual facilities in classrooms has emerged as a potential catalyst for enhancing the learning experience, particularly in the realm of English Phonology. Through observing classrooms and gathering feedbacks from both educators and students, a clearer picture of the impact of audiovisual tools emerged. The ease of illustrating phonetic and phonological nuances with the help of visual and auditory stimuli was found to significantly elevate the learning curve. The interaction between visual aids, auditory tools, and traditional teaching methods creates a more engaging and interactive learning environment, which in turn, contributes to a more effective motivating and enjoyable learning experience. This exploration has not only shed light on the potential benefits of employing audiovisual facilities in the teaching and learning of English Phonology but also advocated for a broader acceptance and implementation of technology in educational settings to better cater for the diverse learning needs and preferences of today’s learners especially, in English Phonology. These include the compelling need to equip educators with the necessary training on how to effectively use AV facilities to teach English Phonology, enhance resource availability, overcome language interference as well as address technical issues. Others are to foster student engagement, assess effectiveness regularly, explore multimodal learning environments, among others.